Stability of charged density waves in InAs nanowires in an external magnetic field. (2nd November 2017) - Zhukov, A A; Volk, Ch; Winden, A; Hardtdegen, H; Schäpers, Th
Abstract: We report on magnetotransport measurements at T = 4.2 K in a high-quality InAs nanowire ( R w i r e ∼ 20 kΩ) in the presence of the charged tip of an atomic force microscope serving as a mobile gate. We demonstrate the crucial role of the external magnetic field on the amplitude of the charge density waves with a wavelength of 0.8 μ m. The observed suppression rate of their amplitude is similar or slightly higher than the one for weak localization correction in our investigated InAs nanowire.